An Assessment of the Impact of Digital Technology (DT) on Small and Medium Enterprises (SMEs): A Case Study of Some Selected SMEs in La - Adijat Olubukola Olateju (International Journal of Sustainable Applied Sciences, 2024)
This research examines the impact of Digital Technology on Small and Medium Enterprises (SME) activities (in terms of profits and business expansion). The selected sample was 320 SMEs which included 150 SMEs that adopted Digital Technology in their business activities and 170 SMEs that did not adopt Digital Technology in their business but were in the same business field as those that adopted DT. Questionnaires are used to obtain information from these SMEs. Data were analyzed using descriptive statistics (frequency and percentage) and econometric analysis [Propensity Score Matching (PSM)]. The results obtained from the PSM analysis show that the implementation of DT has helped business expansion in the study area among SMEs that adopted DT compared to SMEs that did not adopt DT. However, the implementation of DT has not had a significant impact on the profits of SMEs in the study area compared to non-participating SMEs in DT. Therefore, it is suggested that the adoption of DT is highly recommended among SMEs as this tends to increase business expansion. On the other hand, so that the impact of DT can be felt on entrepreneurs' profits, the costs of implementing DT must be reduced through assistance in the form of grants, subsidies, tax exemptions, tax holidays, and free consultation services in the field. DT areas and loans at lower interest rates should be provided by authorities and stakeholders to encourage SMEs to adopt digital technologies in their businesses.